Evaluasi Lapang Rekomendasi Pemupukan Padi Sawah Berdasarkan Pemupukan Hara Spesifik Lokasi Berbasis Internet di Jawa Tengah Indonesia - Samijan, Samijan; Prastuti, Tri Reni; Warsito, Warsito (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2017)
At the recent, guide of Site Specific of Nutrient Management (SSNM) was developed by International Rice Research Institute (IRRI) in collaboration with Indonesia Agency for Agriculture Research and Development (IAARD) through online media based on internet website. To establish this recommendation technology, field evaluation of SSNM online application based on NM-Rice website was conducted. The assessment was conducted in Trayu and Dukuh Village of Banyudono Sub District of Boyolali District of Central Java Indonesia on dry season 2013 (May-September 2013). The assessment result showed that SSNM rice yield of about 63,2% of farmers in Trayu Village higher than FFP. Yield gap difference of SSNM online varied about 1-20% higher than FFP, whereas the others are almost similar until lower than FFP yield, by variation about 1-11%. The assessment of fertilizer recommendation in Dukuh Village showed that only about 33,3% of farmers cooperator have SSNM yield higher than FFP. Whereas, the others have SSNM online yield lower than FFP which its involved about 10% of farmers have similar yield between SSNM and FFP. An average of NPK rate of SSNM online in Trayu Village is lower than FFP. SSNM online rate for N fertilizer recommendation in this location are about 133 kg/haÂ  (93,9% lower than FFP), P2O5 about 38 kg/ha (73,8% lower than FFP), and K2O about 38 kg/ha (14,5% lower than FFP). Whereas in Dukuh Village, N rate of SSNM online recommendation are about 131 kg/ha (109,7% lower than FFP), P2O5 about 31 kg/ha (29,3% higher than FFP) and K2O about 30 kg/ha (63,3% higher than FFP). Generally, fertilizer recommendation based on SSNM online have benefit about 4,43% from existing.